Profil Hematologi Pekerja Operator PT. PLN Sektor Kapuas PLTD Sungai Raya Pontianak - Diah Wulandari Rousdy, Nisaa Madyan Fadilah, Ari Hepi Yanti (Universitas Tanjungpura, 2016)
Diesel Power Plant (PLTD) is an industry that uses diesel machines as electrical energy plant source. The machines which in PLTD create the sound intensity that exceeds the threshold value which can lead the workers to physiology stress. This research aims to determine the intensity of machines sound noise and hematological profile of PLTD operator workers differences that exposed to the sound of Sungai Raya PLTD machine based on their working period. This research was conducted from October to December2015. Samples which taken as many as 25 operator workers and 6 people carriers as control. The results showed that workers who exposed to machines sound while in the operator room of 80.84 dB and in the engine room of 105.24 dB. The intensity of diesel machines sound in engine room exceeds the threshold value of 85 dB that stipulated in the Decree of the Minister of Environment No. 48 of 1996. Operator workers with working period of 0-5 years has the number of leukocytes, LED level, the percentage ofneutrophils and monocytes higher compared to the control group and a longer working period. In contrast, the number of erythrocytes, hemoglobin levels and lymphocyte percentage of the operator workers 0-5 years lower than in the control group and the other working period. The percentages of hematocrit, eosinophils and basophils operator workers are no different to the control group and other working periods.Workers with longer working period have a body function that has been adapted to the working environment.